The Use of Explicit Instruction in Writing Amongst Students of Colleges of Education in the Ashanti Region of Ghana - Yaa Asantewaa Bediako (European Scientific Journal, ESJ, 2021)
The study sought to examine the use of Explicit Instruction in writing lessons at some selected Colleges of Education in the Ashanti Region of Ghana. The collective case study design informed by constructivist grounded theory data analysis methods was used. Data were collected and analyzed using three instruments namely a semi-structured interview, sample texts on argumentative and expository essays and observations. The study revealed that combining the cognitive strategy of text structure knowledge application with the metacognitive strategy of self-monitoring supports the development of academic writing in students in the Colleges of Education. Also, students make mistakes in their writing and these mistakes include verb errors, article errors and wrong words. It was also revealed that with regards to Explicit Instruction in the classroom, tutors comprehensively used instructions in the language class to enhance students writing skills. This study further showed that tutors have a variety of evidence-based instructional practices that improve many different skills and student’s writing knowledge. The researcher recommended that students in Colleges of Education in Ghana are made to read extensively outside the curriculum to broaden their vocabulary repertoire so that the over-reliance on tutors for corrections can be minimized.